An introduction to staff development in academic libraries [electronic resource] - Connor, Elizabeth (Routledge, 2009)
Suitable for librarians in various roles, this book demonstrates the necessity and value of integrating the library's mission statement and strategic plan with bold approaches to staff orientation,